Draft Annual Plan (2010-11) Volume II Government of Assam - Planning Commission (Planning Commission, 2010)
The Hill Areas of Assam comprising of Karbi Anglong and North Cachar Hills districts cover a geographical area of 15,322 Sq. km. with a total population of 10,01,390 persons as per 2001 Census. Thus, the two hill districts account for 19.5% of the State’s total geographical area and 3.6% of the State’s total population. Both the Hill districts of Assam are predominantly inhabited by Schedule Tribes. While the Karbi Anglong district is mainly inhabited by the Karbi tribes, in the N.C. Hills district, the principal tribe is the Dimassa Kacharis. Besides, many other tribes viz., Zeme Nagas, Hmar, Kukis, Hrangkhol, Biate, Vaiphai, Pnar, Synteng, Jaintias, Mizos, Rengma Nagas, Khasis, Khelma, Bhoi etc. are inhabiting the two hill districts.
Planning and Development Department Dispur